Implementasi Kebijakan Hutan Pendidikan (Studi pada Dusun Sumbersari, Desa Tawangargo, Malang) - Fiulaizi, Anna; Sujarwoto, Sujarwoto; Sentanu, I Gede Eko Putra Sri (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2021)
This paper aims to explain and analyze the implementation of educational forest policy with the implementation model as administrative and political process from Grindle (1980), study on the UB Forest employee forest. The results of this study indicate that the implementation of education forest policy in UB forest is still difficult and be potential for failure. The failure is due to the achievement of the objectives of UB Forest, the program of activities which have not been carried out according to the programs design, and have not yet impacted to social group. This is influenced by various aspects of both the contents of the policy, which includes a) the interests affected; b) type of benefits; c) extend of change envision; d) site of decision making; e) program implementor, and f) resources committed, and the contect of implementation, which includes three (3) aspects; a) power, interests and strategies of the actors involved; b) institutionand regime characteristic; c) compliance and responsiveness.